The Effect of Understanding Fixed Asset Management and Auditor Integrity towards the Quality of Audit report at Regional Inspectorate of Gorontalo Province - Paneo, Yulnaningsih; Hato, Rosman; Pakaya, Abdul Rahman; Sulila, Ismet (Journal of Community Research and Service, 2020)
This research aims to find out The Effect of Understanding Fixed Asset Management and Auditor Integrity towards the Quality of Audit report at Regional Inspectorate of Gorontalo Province partially and simultaneously. Its approach is quantitative, while the method is expost facto. In addition, the research design is causality. The technique of data analysis is multiple regression. The findings reveal that (1) understanding fix asset management influences positively and significantly towards the quality of audit report at Regional Inspectorate of Gorontalo Province with an effect level of 62,60%. The better the understanding of auditor on fixed asset management, the better the quality of audit report Regional Inspectorate of Gorontalo Province. (2) auditor integrity influences positively and significantly towards the quality of audit report at Regional Inspectorate of Gorontalo Province with an effect level of 66,10%. The better the auditor integrity in running the tasks mandated to him/her, the better the quality of audit report at Regional Inspectorate of Gorontalo Province. (3) understanding fixed asset management and auditor integrity simultaneously influence positively and significantly towards dependent variable (the quality of audit report at Regional Inspectorate of Gorontalo Province has determination value of 72,00% while the rest 28,00% can be explained by other variables such as objectivity, audit time pressure, organizational commitment, work loyalty, dysfunctional behavior and technical guidance related to intense and routine investigation.